KONSTITUSIONALITAS PERMENKUMHAM NOMOR 02 TAHUN 2019 PENYELESAIAN KONFLIK NORMA MELALUI MEDIASI - Dewi, Anjaly Rosdiansyah; Hadi, Syofyan (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Minister of Law and Human Rights Regulation No. 2 of 2019 concerning Disharmony Settlement Laws and Regulations Through Mediation regulates the mediation process for disharmony of several regulations such as Ministerial Regulation; Regulation of Non-Ministerial Government Institutions; Regulations from Non-Structural Institutions; and Regional Regulations. Whereas if a regulation is in conflict with other regulations, then a judicial review can be conducted to the Supreme Court and this has been stipulated in the 1945 Constitution where the 1945 Constitution is the highest statutory regulation and there is no lower statutory regulation that can override the provisions The 1945 Constitution. This type of research can be classified as a type of normative research. In this study, the focus is to examine the level of synchronization of law and the principle of law, namely the principle of lex superior derogate legi inferior. Source of data used secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials, data collection techniques in this study with the literature review method, after the data collected and then analyzed to draw conclusions. From the results of research and discussion, it can be concluded that, First, the authority of the Ministry of law and human rights in completing the disharmony of laws and regulations based on Minister of Law and Human Rights Regulation No. 2 of 2019 is something that violates higher legal norms or norms. Because the 1945 Constitution which gives the authority to examine the legislation under the law against the law is to the Supreme Court and not to other institutions. Second, the Supreme Court should conduct a judicial review in which the ideal concept of authority is regulated in the 1945 Constitution and not the Ministry of Law and Human Rights. If you want to test the statutory regulations, then the laws and regulations must be made in the form of laws